2017
DOI: 10.1080/15376516.2017.1388459
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of oxalate-enriched spinach extract as an improved methodology for the induction of dietary hyperoxaluric nephrocalcinosis in experimental rats

Abstract: Experimental induction of hyperoxaluria by ethylene glycol (EG) administration is disapproved as it causes metabolic acidosis while the oral administration of chemically synthesized potassium oxalate (KOx) diet does not mimic our natural system. Since existing models comprise limitations, this study is aimed to develop an improved model for the induction of dietary hyperoxaluria, and nephrocalcinosis in experimental rats by administration of naturally available oxalate rich diet. Male albino Wistar rats were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
2
0
1
Order By: Relevance
“…The range of oxalic acid mass fraction was 6.0−12.2 mg/g. Similar values were recorded by Akhtar et al ( 34 ) and Savage et al ( 35 ) in raw or boiled spinach and they were ten times lower than those found by Albert et al ( 36 ) in dried spinach water extract. Average oxalate dry mass fraction in this study was 8.97 mg/g whereas Wang et al ( 4 ) observed higher average oxalate mass fraction on fresh mass basis of 20.76 mg/g.…”
Section: Resultssupporting
confidence: 88%
“…The range of oxalic acid mass fraction was 6.0−12.2 mg/g. Similar values were recorded by Akhtar et al ( 34 ) and Savage et al ( 35 ) in raw or boiled spinach and they were ten times lower than those found by Albert et al ( 36 ) in dried spinach water extract. Average oxalate dry mass fraction in this study was 8.97 mg/g whereas Wang et al ( 4 ) observed higher average oxalate mass fraction on fresh mass basis of 20.76 mg/g.…”
Section: Resultssupporting
confidence: 88%
“…Although increased urinary oxalate excretion and its dietary consumption are directly linked to kidney stones, oxalate crystal deposition in renal parenchyma is also responsible for nephrocalcinosis [ 102 ]. Mice fed with an oxalate-added spinach-derived extract developed crystalluria, hyperoxaluria and interstitial inflammation associated to nephrocalcinosis [ 103 ]. In humans affected by cystic fibrosis, the presence of absorptive hyperoxaluria has been linked to both nephrolithiasis and nephrocalcinosis [ 104 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…The potential mechanism might be that Slc26a6 led to the secretion and reabsorption of oxalate, resulting in higher oxalate concentration in urine and interstitium ( Marengo & Romani, 2008 ). A high-oxalate concentration could lead to tissue inflammation and crystal deposition in a short time ( Albert et al, 2017 ). Therefore, the lv-Slc26a6 group had the highest level of crystals and the siRNA-Slc26a6 group had the least level of crystals ( Fig.…”
Section: Discussionmentioning
confidence: 99%